(3NhGU GdMTGFT hefGaY GdMjhGfs - (3LGdjfhSs ((3GHh GdHbGA hgHGf Hf GdbS GHQGgje s)
(3ChdgG (B:s
(3HYO GdHSedI (B: (3bGd LGdjfhS GPG hVY YXe GfSGf ejJ jYfi NQSg EPG Ydb Ydi ef Hg hLY NQSg s
(3BNQgG (B:s
(3EVQGQg HGdcHO , EUdGMg HGdcKjQI , NjQg GdHGdZ GdhRf GQHYI OQGge s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa (B- (3U (B187 s
(3eUOQ GbJfGA GdCUd (B:s
(3SGdG QLfL HMjOQ CHGO (B(1958) s
Keywords: (3GdRQGYI h GdCYTGHs